Antioxidative Potential Of Catalase In Bloom Forming Cyanobacteria- Anabaena Variabilis And Synechococcus Elongates - ARCHANA TIWARI; SHIVANI (International Journal of Pharma and Bio Sciences, 2012)
Cyanobacteria are fascinating and versatile group of bacteria which are of immense biological importance. They are unique photosynthetic prokaryotes with an oxygenic photosynthesis process. They possess an array of protective mechanism comprising of antioxidants to eliminate the damages caused by the reactive oxygen species. Blooms caused by cyanobacteria are ubiquitous in temple ponds, lakes and other water reservoirs. In this study, the antioxidative potential of catalase in bloom forming cyanobacteria Synechococcus elongatus and Anabaena variabilis was determined. The activity of catalase by spectrophotometric analysis, using hydrogen peroxide as the substrate showed activity 35.45±4.45mM/min/µg protein in Synechococcus elongatus and 13.68±1.09 mM/min/µg protein in Anabaena variabilis. The presence of catalase was also confirmed by native–PAGE, discrete band was visualized after activity staining. Antioxidants have the potential to serve significant role in processing and storage of food and other medicinally important preparations such as dry vaccines. Research on occurrence of antioxidative enzymes and elucidating the mechanisms behind the stability of these enzymes in various systems will open new horizons.